2021
DOI: 10.7150/jca.60379
|View full text |Cite
|
Sign up to set email alerts
|

Colony Stimulating Factor-1 and its Receptor in Gastrointestinal Malignant Tumors

Abstract: Gastrointestinal malignant tumor is the fourth most common cancer in the world and the second cause of cancer death. Due to the susceptibility to lymphatic metastasis and liver metastasis, the prognosis of advanced tumor patients is still poor till now. With the development of tumor molecular biology, the tumor microenvironment and the cytokines, which are closely related to the proliferation, infiltration and metastasis, have become a research hotspot in life sciences. Colony stimulating factor-1 (CSF-1), a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…CSF1 primarily functions in the regulation of the immune system 79 . Elevated levels of CSF1 in plasma have been associated with various diseases and conditions, including inflammation, cancer, and certain autoimmune disorders [80][81][82] . Taken together, these findings suggest that widespread systemic inflammation may also manifest in the plasma of individuals with AD.…”
Section: Discussionmentioning
confidence: 99%
“…CSF1 primarily functions in the regulation of the immune system 79 . Elevated levels of CSF1 in plasma have been associated with various diseases and conditions, including inflammation, cancer, and certain autoimmune disorders [80][81][82] . Taken together, these findings suggest that widespread systemic inflammation may also manifest in the plasma of individuals with AD.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in our study immunoinhibitors, CSF1R, HAVCR2, and LGALS9, were found to be associated with LOXL3, while TGFB1, TGFBR1, and VTCN1 correlated with LOX. CSF-1R plays critical roles in regulating tumorassociated macrophages in TME, and targeted inhibition of the CSF-1/CSF-1R signal axis has broad application prospects in immunotherapy of malignant tumors (74). Pexidartinib is an orally administered small-molecule tyrosine kinase inhibitor that selectively inhibits CSF1R, and is currently being assessed for other types of cancer (75).…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 gene encodes the CD4 membrane glycoprotein of T lymphocytes and acts as an important mediator in immune regulation [14]. CSF-1 is an important cytokine that directly acts on its receptor CSF-1R, is involved in the regulation of tumor-related macrophages, and plays an essential role in the occurrence and development of diverse cancers [15]. Thus, further experiments were performed to investigate CSF-1R for its clinical meaning.…”
Section: Ppi Network Construction and Module Analysismentioning
confidence: 99%